PENENTUAN PRIORITAS JENIS AGROINDUSTRI KELAPA DI KABUPATEN HALMAHERA BARAT - Relanti Irene Sopacua; Anna Fariyanti; Burhanuddin Burhanuddin (Forum Agribisnis, 2020)
The main source of farmer households in West Halmahera is coconut plantations. Coconut fruit is produced, some are sold in the form of whole fruit, some are processed into copra. For this agro-industry development effort to work effectively, it is necessary to determine the type of coconut agroindustry that will be developed by considering the factors that increase, the efforts of the businesses involved and the objectives of each of the agro-industries. The purpose of this study was to determine the priorities of coconut agro-industry that had to be developed in West Halmahera Region. The data were analyzed using the Process Hierarchy Analysis (AHP) approach and internal-external factor. The results showed that the virgin coconut oil (VCO) agro-industry had the highest priority in the development of coconut agro-industry in West Halmahera. By the development of this agro-industry, business actors will gain added value, affect the increase in income, and will open new jobs in the rural area. The important factors that have influenced the development of agro-industry were human resources (HR) and asset. Furthermore, each actor involved has a firm role and linkage to each of the determinants of agro-industry business development. Farmers have the main role (37%) on the availability of raw materials, farmer groups have strong correlation (42%) to human resources, the government plays an important role (42%) in infrastructure development, and academics have an enormous contribution (34%) in providing technology for the development of agro-industry. Overall, the most important actors in the development of coconut agro-industry in West Halmahera are farmer groups. The Strategy applied to agro-industry virgin coconut oil (VCO) at West Halmahera Region is intensive: market penetration, market development and product development.